EMOTIONS, FEELINGS AND AFFECTS IN EARLY FRENCH ROMANTICISM: PROBLEMS OF STUDY (the first article) - Ninel A. Litvinenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2020)
The article substantiates the relevance of updating the anthropological approach to the study of romanticism in connection with the achievements of modern psychological science. This makes possible to deepen literary ideas about the specifics of the depiction of the inner world of characters and the peculiarities of the psychological skill of the writers of early French romanticism. The study of the anthropology of Romanticism, despite the multitude of works devoted to this problem, remains of literary relevance. This is due to the inexhaustibility of the phenomenon, covering various areas of art; the emergence of new methodologies, interdisciplinary approaches, allowing to rethink the seemingly quite literary proven material. The study of the heritage of French Romanticism, which went through several stages of evolution in the 19th century, the interaction with other literary movements, such as Sentimentalism, Realism, Symbolism, Naturalism, is in touch with these processes. Feelings, sensations, impressions, real and fictitious, all vibrations and threads connecting the individual with society and the world, the states experienced by him acquire in Romanticism an invaluable and valuable dimension, penetrating deeply into the sphere of moral issues, morality, personal and social, forming new vectors of evolution of psychology, philosophy and ethics. All the aesthetic categories – the sublime, the beautiful, the tragic, the comic, and their associated invariants and perceptions, participating in new syntheses, become the components of new subjectively and subjectively organized worlds and antinomies. Feelings, emotions, and affects take part in artistic myth-making and become the privileged sphere of cognition and self-cognition of the subject – poet, writer, and artist. The creative process, as well as the reader’s perception, affects different aspects of created « emotional modes» not only in poetry, drama, but also in prose, especially as the boundaries separating these fields of art since classical times have sometimes been completely erased, new genres have emerged and the processes of genre diffusion and interaction have increased. Early French Romanticism, the novels of Chateaubriand, Germaine de Stael, partly Senancour, B. Constant transformed the experience of predecessors, techniques and notions related to the specifics of embodiment of the psychology of a modern man, his emotions and feelings – the experience accumulated by 18th century literature, including Voltaire and Diderot, Prevost and Marivaux, Rousseau and Bernardin de Saint-Pierre, Goethe. The authors’ space of emotions, feelings, sensibilities, affects and personal behaviour patterns in early French Romanticism acquired new dynamics, new vectors of historical and psychological evolution.